Perception and Prevalence of Bullying Among Junior High School Students of Biliran Province State University - Jovy Dia R. Saniel; Charlotte C. Opeña; Joice Balondo Balondo; Allyza Mariz B. Bunda; Liezl B. Tambis (Pediomaternal Nursing Journal, 2021)
Introduction: A school is where a student learns and molds into the desired individual but sometimes, a place where the famous and beautiful are honored and respected while the poor little ones are experience bullying. This study aims to determine the perceptions and prevalence of bullying to design a plan addressing issues on students' predicaments in Biliran Province State University (BiPSU).Methods: The researchers made use of the Statistical Package for the Social Sciences (SPSS)-Descriptive Statistics’ frequency, percentile and central tendency, where variables as to profile, perception and prevalence of  bullying among secondary students  are statistically analyzed.Results: Students' perception of bullying is significant than its prevalence. Students have increased knowledge and awareness of bullying. However, though less notable than the perception, the pervasiveness of bullying is still considerable.Conclusion: The majority of the respondents have not experienced bullying. Students think that bullying at school happens once or twice a term. Student's perception of bullying is more eminent than its prevalence. These pervasion results are meaningful because students' reflection in bullying is distinguished.